Formation of stress resilience in adolescents through training in performing arts - Asylzat Ibraeva; Ulzharkyn Abdigapbarova; Laura Shalabayeva; Nadezhda Zhiyenbayeva (International Journal of Adolescence and Youth)
This research aimed to investigate the impact of performing arts on enhancing resilience in Kazakhstani adolescents, comparing these effects with those experienced by a control group engaged in regular educational activities. A longitudinal approach was applied to 300 adolescents aged 13–17, divided into an experimental group participating in performing arts and a control group following a standard educational curriculum. The Connor-Davidson Resilience Scale (CD-RISC-25) was utilized to measure resilience at three key points: baseline, midpoint, and post-intervention. Interestingly, both the experimental and control groups demonstrated similar improvements in resilience over time. Mean resilience scores slightly increased in both groups, and secondary ANOVA analysis revealed no significant differences based on gender or group participation (p ≥ 0.05). This trend persisted across baseline, midpoint, and post-intervention measurements, indicating a general improvement in resilience among all participants, regardless of their involvement in performing arts.